Continuous thermosalinograph oceanography along RV MARIA S. MERIAN cruise track MSM127/1 - Schlundt, Michael; Freudenthal, Tim (PANGAEA, 2025)
Underway temperature and salinity data was collected along the cruise track with two autonomous measurement systems. Usually, the systems are changed after 12 hours. While temperature is taken at the water inlet in about 6.5 m depth, salinity is estimated within the interior measurement container from conductivity and interior temperature. Neither temperature nor salinity calibration was performed. For details to all processing steps see Data Processing Report.